Requisitos e arquiteturas das redes de telefonia móvel de quinta geração - Oliveira, Gabrielli Mariana de (2021)
Mobile communications have a trajectory defined by exponencial advancement, compared to emerging technologies that are constantly emerging. Although some regions still do not have it in place, 4G, as fifth generation networks, have already been mapped and designed to meet the high market demand connectivity. The main objective of lhe work is to present an in-depth analysis of 5G networks, starting from lhe requirements and specifications expected for the system and covering ali emerging technologies that were allocated to structure the network architecture of this generation. We propose, therefore, a brief study of possible cases of use and deployments when integrated into scenarios where mobile communication goes beyond telephony and Internet access, describing services specific to certain market sectors. From this perspective, a generalized perspective on the insertion of 5G in the Brazilian market is defined to illustrate and point out the challenges faced by operators facing the 5G auction and the integration of the network throughout the Brazilian territory. The final analysis will be given towards possible future plans both for the definition of a next generation, and for implementing and achieving ali the expected requirements of 5G.